El arte en la educación de la primera infancia: una necesidad impostergable - Mendívil Trelles de Peña, Luzmila (Pontificia Universidad Católica del Perú. Fondo Editorial, 2011)
Art in early childhood education: An ineluctable needThe present essay focuses on the need for educational institutions, especially those working with early childhood, to recover art as a central issue in the education of young children, both in relation to the demands of the new century demands, as well in response to the most authentic needs of every human being. It also addresses the role of art in the development of inherent capacities not only to individual areas, linked to creativity, imagination, and the development of the scientific attitude, but those of social nature that include the construction of personal and cultural identity, as well as the skills required to live with others, and those leading to social change.

El presente ensayo gira en torno a la necesidad que tienen las instituciones educativas, especialmente aquellas que trabajan con primera infancia, de recuperar el arte como un tema central en la educación del niño pequeño, tanto de cara a lasdemandas del nuevo siglo, como también en respuesta a las necesidades más auténticas de todo ser humano. Asimismo aborda la función del arte en el desarrollo de capacidades inherentes no solo a los ámbitos personales, vinculados a la creatividad, la imaginación, y el desarrollo de la actitud científica; sino aquellas de índole social que comprenden la construcción de la identidad personal y cultural, las habilidades requeridas para la convivencia y las que conducen al cambio social.
Keywords: Arte; Cambio Social; Educación de la Primera Infancia; Identidad; Cultura; Art; Social Change; Early Childhood Education; Identity; Culture; https://purl.org/pe-repo/ocde/ford#5.03.00